1981
DOI: 10.1161/01.cir.63.2.378
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanism of action of aminophylline on cardiac function and regional blood flow distribution in conscious dogs.

Abstract: SUMMARY The effects of aminophylline, 1 mg/kg/min infused intravenously for 10 minutes, were examined on left ventricular (LV) diameter, pressure, and indexes of myocardial contractility, as well as systemic, coronary and regional hemodynamics in conscious dogs. Aminophylline increased mean arterial pressure 12 i 2%, LV systolic pressure 8 ± 1%, LV dP/dt 20 ± 2%, velocity of myocardial fiber shortening 13 ± 2% and heart rate 5 ± 2%, and reduced LV end-diastolic diameter 2 ± 0.5%. Vascular resistance rose in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 20 publications
1
15
2
Order By: Relevance
“…The hypothesis that the vasoconstrictor effect of methylxanthines involves catecholamines is supported by the observation that the increase of vascular resistance caused by aminophylline in the conscious dog is attenuated by a-adrenergic blockade. 39 Of note, in our study, bamiphylline did not affect heart rate or arterial blood pressure under resting conditions, suggesting that prejunctional A1 adenosine receptors are not active at rest. Another potential mechanism by which bamiphylline can limit subepicardial perfusion might be inhibition of ATP-sensitive potassium channels.…”
Section: Anti-ischemic Effects Of Bamiphyllinecontrasting
confidence: 47%
“…The hypothesis that the vasoconstrictor effect of methylxanthines involves catecholamines is supported by the observation that the increase of vascular resistance caused by aminophylline in the conscious dog is attenuated by a-adrenergic blockade. 39 Of note, in our study, bamiphylline did not affect heart rate or arterial blood pressure under resting conditions, suggesting that prejunctional A1 adenosine receptors are not active at rest. Another potential mechanism by which bamiphylline can limit subepicardial perfusion might be inhibition of ATP-sensitive potassium channels.…”
Section: Anti-ischemic Effects Of Bamiphyllinecontrasting
confidence: 47%
“…At these concentrations in vitro, theophylline is a very weak inhibitor of phosphodiesterase activity3638 and is not associated with an elevation in tissue levels of cyclic AMP.39'40 Although 10 ,uM theophylline relaxed carbachol contracted bovine tracheal muscles by 85-95%,39 similar concentrations had little or no effect in isolated heart muscle preparations.40'4' Perfusion of the canine sinus node artery with low concentrations of aminophylline (1-10 ,ug/ml) did not cause a change in heart rate, but a much higher concentration (100 ,ug/ml) resulted in an immediate tachycardia. "I Rutherford et al 13 observed positive inotropic, chronotropic and pressor responses after i.v. aminophylline, 10 mg/kg, in the conscious dog.…”
Section: Plasma Epinephrine and Norepinephrinementioning
confidence: 97%
“…In contrast to systemic administration, direct infusion of aminophylline into the iliac artery resulted in vasodilatation. These investigators and others'1 13,42 have proposed that the cardiac and hemodynamic effects of theophylline may be explained, at least in part, by the release of endogenous catecholamines. Our findings that plasma catecholamines increase during theophylline administration in man also supports this hypothesis.…”
Section: Plasma Epinephrine and Norepinephrinementioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in both global myocardial performance (Parker et al 1966b;Falicov et al 1973;Rutherford et al 1981;Matthay 1985;Matthay & Mahler 1986) and right heart performance have been demonstrated with intravenous aminophylline (Bisgard & Will 1977;Matthay et al 1978). It is difficult, however, to decide how much an improvement in left ventricle function (e.g.…”
Section: Discussionmentioning
confidence: 99%